Concurrent Benign Metastasizing Leiomyoma in the Abdominal Wall and Pelvic Cavity: A Case Report and Review of the Literature - Li, Yue; Xu, Tongtong; Wang, Mingdan; Jiang, Lili; Liu, Qifang; Liu, Kuiran (Frontiers in Surgery, 2022)
Benign metastasizing leiomyoma(BML) is a rare histologically benign disease with invasive biological behavior, usually occurring in women of reproductive age with a history of uterine leiomyoma.BML mostly has an indolent clinical course and follows a favorable prognosis.The lung is the most frequently affected organ, and the incidence of expulmonary BML is very low. We report an unusual case of BML both in the abdominal wall and pelvic cavity in a 37-year-old woman admitted to our hospital.The purpose of this case report is to explore the pathological characteristics, diagnosis, differential diagnosis, and treatment for BML.